Applying Theories of Communal Motivation to Sexuality. Issue 8 (August 2016) - Muise, Amy; Impett, Emily A.
Abstract: One important but challenging aspect of maintaining a satisfying romantic relationship is keeping the sexual spark alive. Research suggests the importance of a couple's sexual connection in the maintenance of their relationship, but sustaining high levels of desire for a partner over the course of time can be difficult. In the current review, we argue that one novel approach to understanding how couples might maintain desire and satisfaction over the course of time in their relationships is applying theories of communal motivation to the domain of sexuality. In this line of research, we have demonstrated that people high in sexual communal strength – those who are motivated to be non‐contingently responsive to their partners' sexual needs – are able to sustain higher sexual desire over the course of time and navigate sexual disagreements in a way that maintains both partners' relationship quality. Future research directions include broadening the view of sexual needs to include the need to decline or reject a partner's sexual advances and investigating how partners manage unmet sexual needs.